Family satisfaction following spinal fusion in Rett syndrome. (2nd January 2016) - Downs, Jenny; Torode, Ian; Ellaway, Carolyn; Jacoby, Peter; Bunting, Catherine; Wong, Kingsley; Christodoulou, John; Leonard, Helen
Abstract: Purpose : We evaluated family satisfaction following spinal fusion in girls with Rett syndrome. Methods : Families participating in the population-based and longitudinal Australian Rett Syndrome Database whose daughter had undergone spinal fusion provided data on satisfaction overall, care processes and expected changes in health and function. Content analysis of responses to open-ended questions was conducted. Results : Families reported high levels of overall satisfaction and consistently high ratings in relation to surgical and ICU care. Outstanding clinical care and the development of strong partnerships with clinical staff were much appreciated by families, whereas poor information exchange and inconsistent care caused concerns. Conclusions : Family satisfaction is an important outcome within a patient-centred quality of care framework. Our findings suggest strategies to inform the delivery of care in relation to spinal fusion for Rett syndrome and could also inform the hospital care of other children with disability and a high risk of hospitalization.